Respiratory tract infection and bronchial responsiveness in elite athletes and sedentary control subjects - Heir, T.; Aanestad, G.; Carlsen, K. H.; Larsen, S. (Scandinavian Journal of Medicine & Science in Sports, 1995)
To assess the effect of physical exercise during an acute respiratory tract infection (RTI) on bronchial responsiveness, methacholine bronchial challenge tests were performed prospectively in 19 nonasthmatic male cross-country skiers and 22 healthy control subjects with minimal physical activity. Twelve skiers and 10 controls contracted RTI and were studied before and 1, 3 and 6 weeks after the onset of symptoms. The skiers were given no restrictions in their training routines during the period of illness. The geometric mean provocation concentration of methacholine causing a 10% fall in the forced expiratory volume in the first second (PC10), was lower 1 week after onset of infection than at the initial test in the skiers. From the level at 1 week, PC10 increased to levels at 3 and 6 weeks after infection. The PC10 values at 3 and 6 weeks were not significantly different from the initial test. No significant changes in PC10 occurred after infection in the control group. No significant changes in pulmonary function tests were found during the study period in either of the two groups. In conclusion, RTI was associated with a transient increase in bronchial responsiveness in athletes performing physical training during the symptomatic period of respiratory illness but not in nonactive control subjects.